Syntactic features of advertising slogan in the English language and its translation into Russian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The main syntactic techniques of slogan making are studied in the article. Such techniques as elliptical constructions, syntactic repetition, parallelism, parceling are defined. The translations of some slogans are analysed, due to their syntactic structure and its preservation in the translation.
Keywords: slogan; syntactic technique; elliptical constructions; syntactic repetition; parallelism; parceling